High performance floating self-excited sliding triboelectric nanogenerator for micro mechanical energy harvesting - Li Long (Nature Portfolio, 2021)
High reliability is a huge challenge for sliding mode triboelectric nanogenerator (TENG). Here the authors develop a floating self-excited sliding TENG achieving both high durability and output for sustainable micro mechanical energy harvesting.